2015
DOI: 10.1186/s12879-015-0757-7
|View full text |Cite
|
Sign up to set email alerts
|

Do Australian general practitioners believe practice nurses can take a role in chlamydia testing? A qualitative study of attitudes and opinions

Abstract: BackgroundChlamydia notifications continue to rise in young people in many countries and regular chlamydia testing is an important prevention strategy. Although there have been initiatives to increase testing in primary care, none have specifically investigated the role of practice nurses (PNs) in maximising testing rates. PNs have previously expressed a willingness to be involved, but noted lack of support from general practitioners (GPs) as a barrier. We sought GPs’ attitudes and opinions on PNs taking an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…It is also interesting to note there may be some disparity between PNs’ perception of GP attitudes and the actual attitudes of GPs. In a series of qualitative interviews with 44 GPs undertaken as part of ACCEPt, the vast majority supported the concept of PN chlamydia testing, identifying similar benefits to their involvement as were raised by the PNs in this study [ 32 ].…”
Section: Discussionmentioning
confidence: 81%
“…It is also interesting to note there may be some disparity between PNs’ perception of GP attitudes and the actual attitudes of GPs. In a series of qualitative interviews with 44 GPs undertaken as part of ACCEPt, the vast majority supported the concept of PN chlamydia testing, identifying similar benefits to their involvement as were raised by the PNs in this study [ 32 ].…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, as the 3Cs and HIV is a complex intervention with multifaceted components and outcomes, a specific action plan detailing staff’s roles and responsibilities to implement the intervention should have been agreed at the end of the training session and re-visited at practice meetings [44, 45]. …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, more specificity was necessary in regards to where the posters should have been displayed, as the educational workshops suggested that posters displayed in consultation rooms could be used as a prompt or conversation starter, but this was not always adhered to. Furthermore, as the 3Cs and HIV is a complex intervention with multifaceted components and outcomes, a specific action plan detailing staff’s roles and responsibilities to implement the intervention should have been agreed at the end of the training session and re-visited at practice meetings [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Australian primary care nurses indicated that the provision of training, streamlining chlamydia testing and simplification of pathology ordering processes would also facilitate nurses’ chlamydia testing. 19 As other work has found little significant difference in GP care provision in our four countries involved, 4 the intervention should be easily transferable. In Sweden and England, sexual health is established in the GP medical training curriculum, 4 which will facilitate implementation, whereas in France, sexual health training was not mandatory and in Estonia, it was extremely limited.…”
Section: Strengths and Limitationsmentioning
confidence: 88%
“…It is interesting that the barriers to chlamydia testing in general practice we identified in this study are similar to those identified across primary care settings: in England 17 18 and Australia. 19 20 Continued barriers to sexual health provision in general practice indicate that behaviourally based interventions are needed to allow chlamydia testing to become embedded in routine practice. GP staff in the previous CIRT study who successfully increased their practice’s chlamydia screening 21 had implemented many of the suggestions made by staff in the other countries of this study, including: computer prompts that helped staff remember to make the offer, having a designated lead and feedback about the general practice’s testing rates.…”
Section: Strengths and Limitationsmentioning
confidence: 99%